2017
DOI: 10.1002/art.40036
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Baricitinib on Lipid, Apolipoprotein, and Lipoprotein Particle Profiles in a Phase IIb Study of Patients With Active Rheumatoid Arthritis

Abstract: Baricitinib-associated increases in serum lipid levels were observed in this study. Increases in levels of HDL cholesterol correlated with improved clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 26 publications
3
25
1
2
Order By: Relevance
“…The study by Fleischmann et al (19) was ignored due to the combined use of baricitinib and methotrexate (MTX). A total of 4 studies were eliminated due to the lack of available data for analysis (2023). Finally, 7 RCTs were selected, including 2 phase-II (24,25) trials and 5 phase-III trials (3,2629).…”
Section: Resultsmentioning
confidence: 99%
“…The study by Fleischmann et al (19) was ignored due to the combined use of baricitinib and methotrexate (MTX). A total of 4 studies were eliminated due to the lack of available data for analysis (2023). Finally, 7 RCTs were selected, including 2 phase-II (24,25) trials and 5 phase-III trials (3,2629).…”
Section: Resultsmentioning
confidence: 99%
“… 7–11 Increases in lipids persisted in a phase II study of baricitinib. 12 The increase in LDL-C was associated with an increase in large and a decrease in small LDL, without any increase in LDL particle number. The increase in HDL-C was associated with an increase in HDL particle number across all particle sizes.…”
Section: Introductionmentioning
confidence: 92%
“…The increase in HDL-C was associated with an increase in HDL particle number across all particle sizes. 12 This LDL and HDL particle profile has been associated with reduced atherogenic risk. 13 …”
Section: Introductionmentioning
confidence: 99%
“…However, the role of these agents in the modulation of cardiovascular risk remains undetermined 15 16. Limited evidence suggested that tofacitinib-based therapy positively modifies the risk of cardiovascular disease,17 18 while a growing body of literature indicated that Jakinibs adversely affect several cardiovascular risk factors (such as serum lipid profile and platelet count) and potentially increase thrombotic risk which directly leads the US Food and Drug Administration (FDA) to restrict approval to only 2 mg baricitinib 19–22. Additionally, in upadacitinib premarketing trials, major adverse cardiovascular events (MACEs) continuously reported in patients with RA receiving upadacitinib has further generated cardiovascular concerns 23…”
Section: Introductionmentioning
confidence: 99%